Studi Distribusi Elektron pada Semikonduktor Tipe N dan P sebagai Penyusun Transistor - Duwi Hariyanto; Kisna Pertiwi; Sabar Sabar (Journal of Science, Technology, and Visual Culture, 2021)
The materials used in the production of transistors are N-type and P-type semiconductors. The characteristics of these materials can be determined from the state of the electrons (carriers) in the energy band. Electrons in semiconductors are fermions, so the probability of an electron's state in the energy band is determined by the Fermi-Dirac distribution. The aimed of the study is to examine the distribution of electrons in N-type and P-type semiconductors as transistor materials using simple calculations. The Microsoft Excel software was used to calculate the Fermi-Dirac distribution and the Fermi level. The results of the calculations have a good agreement with the state of the electron and deviations from the Fermi level due to increasing temperature.